Anti-tumour necrosis factor treatment of severe psoriasis complicated by Epstein-Barr Virus hepatitis and subsequently by chronic hepatitis - Cetkovska, Petra; Lomicova, Iva; Mukensnabl, Petr; Kroes, Aloysius C M (Dermatologic therapy, 2015)
A case is described of severe acute hepatitis in 47-year-old woman with chronic psoriasis and psoriatic arthritis treated with infliximab. Although clinical, serological and laboratory results were compatible with acute EBV hepatitis, it was difficult to differentiate between EBV infection and other non-infectious causes of hepatitis. The patient gradually developed chronic hepatitis with liver steatosis and efficient treatment with adalimumab had to be stopped. This case presents an uncommon complication that may arise from the use of biologic therapy and calls for caution in long-term management of psoriatic patients with internal comorbidities.
Keywords: oportunní infekce; Biopsy; Infliximab; Humans; chronická hepatitida; lidé středního věku; Hepatitis, Chronic; Psoriasis; infliximab; Alcohol Drinking; pití alkoholu; Female; rizikové faktory; Hepatitis, Viral, Human; psoriáza; výsledek terapie; lidé; infekce virem Epsteina-Barrové; biopsie; Epstein-Barr Virus Infections; TNF-alfa; virová hepatitida u lidí; indukce remise; hepatitis Epstein-Barr virus; biologic therapy; imunologické faktory; ženské pohlaví; Opportunistic Infections; stupeň závažnosti nemoci; psoriasis; Middle Aged; antivirové látky; Treatment Outcome; Remission Induction; Antiviral Agents; Immunologic Factors; Severity of Illness Index; Tumor Necrosis Factor-alpha; imunokompromitovaný pacient; Immunocompromised Host; Risk Factors